2020
DOI: 10.1101/2020.11.25.398537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling sensory neuron microenvironment after peripheral and central axon injury reveals key pathways for neural repair

Abstract: Sensory neurons with cell bodies in dorsal root ganglia (DRG) represent a useful model to study axon regeneration. Whereas regeneration and functional recovery occurs after peripheral nerve injury, spinal cord injury or dorsal root injury is not followed by regenerative outcomes. This results in part from a failure of central injury to elicit a pro-regenerative response in sensory neurons. However, regeneration of sensory axons in peripheral nerves is not entirely cell autonomous. Whether the different regener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 132 publications
(261 reference statements)
2
36
0
Order By: Relevance
“…To address this, we analyzed a single-cell RNA-Seq data set of naive mouse DRG (Fig 1 , I). 7 We found that Il1rl1 was indeed expressed by another cell type: DRG macrophages (Fig 1 , J). Similarly, analysis of other neuronally expressed itch-associated cytokine receptors, such as Il4ra, 8 revealed expression across numerous cell types ( Fig 1,K).…”
Section: Resultsmentioning
confidence: 69%
“…To address this, we analyzed a single-cell RNA-Seq data set of naive mouse DRG (Fig 1 , I). 7 We found that Il1rl1 was indeed expressed by another cell type: DRG macrophages (Fig 1 , J). Similarly, analysis of other neuronally expressed itch-associated cytokine receptors, such as Il4ra, 8 revealed expression across numerous cell types ( Fig 1,K).…”
Section: Resultsmentioning
confidence: 69%
“…To date, limited studies suggest that satellite glia modulate ionic and neurotransmitter concentrations, promote neuronal morphogenesis, regulate synaptic transmission, and engulf dying neurons (Avraham et al, 2020;Enes et al, 2020;Hanani and Spray, 2020;Wu et al, 2009). Recent studies in sensory ganglia indicate that satellite glia regulate chronic pain through modulating neuronal excitability and promote axon regeneration after nerve injury (Avraham et al, 2020(Avraham et al, , 2021Jager et al, 2020;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that SGC contribute to the nerve repair process in mice (Avraham, Deng, et al, 2020) and that the FDA approved PPARα agonist fenofibrate, which is used in dyslipidemia treatment, can increase axon regeneration after the dorsal root injury, a model of poor sensory axon growth (Avraham, Feng, et al, 2020). Fenofibrate was surprisingly shown in clinical trials to have neuroprotective effects in diabetic retinopathy (Bogdanov, Hernandez, Corraliza, Carvalho, & Simo, 2015;Moreno & Ceru, 2015) and traumatic brain injury (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1a). We chose to perform scRNAseq in rodents because we previously showed that this method efficiently captures SGC (Avraham, Deng, et al, 2020;Avraham, Feng, Ewan, Zhao, & Cavalli, 2020). We opted for snRNAseq in human DRG because the tissue was frozen and the large size of cells in human may limit their capture rate in the 10x platform.…”
Section: Profiling Drg Cells From Human Mouse and Rat At The Single Cell Levelmentioning
confidence: 99%